2020
DOI: 10.1042/bcj20200555
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A negatively regulates VEGF-induced AMPK activation by phosphorylating CaMKK2 at serine 495

Abstract: Activation of AMP-activated protein kinase (AMPK) in endothelial cells by vascular endothelial growth factor (VEGF) via the Ca2+/calmodulin-dependent protein kinase kinase 2 (CaMKK2) represents a pro-angiogenic pathway, whose regulation and function is incompletely understood. This study investigates whether the VEGF/AMPK pathway is regulated by cAMP-mediated signalling. We show that cAMP elevation in endothelial cells by forskolin, an activator of the adenylate cyclase, and/or 3-isobutyl-1-methylxanthine (IBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…14-3-3 protein recruitment by CaMKK1 partly suppresses its catalytic activity, whereas CaMKK2 activity remains unaltered, suggesting different regulation mechanisms for these isoforms [3,70,71,74]. Moreover, it has recently been shown that phosphorylation of CaMKK2 at Ser 495 is involved in regulating VEGF-induced AMPK activation, a pathway shown to regulate angiogenesis [75].…”
Section: Calcium/calmodulin-dependent Protein Kinase Kinases (Camkk)mentioning
confidence: 99%
“…14-3-3 protein recruitment by CaMKK1 partly suppresses its catalytic activity, whereas CaMKK2 activity remains unaltered, suggesting different regulation mechanisms for these isoforms [3,70,71,74]. Moreover, it has recently been shown that phosphorylation of CaMKK2 at Ser 495 is involved in regulating VEGF-induced AMPK activation, a pathway shown to regulate angiogenesis [75].…”
Section: Calcium/calmodulin-dependent Protein Kinase Kinases (Camkk)mentioning
confidence: 99%
“…Protein kinase C (PKC) results in phosphorylation at AMPKα1 Ser487, thereby inhibiting AMPK activity ( Heathcote et al, 2016 ). Vascular endothelial growth factor (VEGF) activates AMPK through CaMKK2 in endothelial cells, but protein kinase A (PKA) inhibits AMPK activation by phosphorylation at Ser495 ( Spengler et al, 2020 ). Further investigation will likely reveal more types of kinases and ensure better understanding of their important roles in AMPK activation and inhibition.…”
Section: Adenosine Monophosphate Activated Protein Kinase and Its Act...mentioning
confidence: 99%
“…This signal transduction results in the regulation of many important physiological and pathological processes. 6 16 …”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, CAMKK2 phosphorylates and activates its substrates including CAMK1, CAMK4, AMP-activated protein kinase, (AMPK) and in some cases AKT. This signal transduction results in the regulation of many important physiological and pathological processes. …”
Section: Introductionmentioning
confidence: 99%